1987
DOI: 10.1093/oxfordjournals.aje.a114515
|View full text |Cite
|
Sign up to set email alerts
|

A Cohort Study of Amyotrophic Lateral Sclerosis and Parkinsonism-Dementia on Guam and Rota

Abstract: A prospective study of the incidence of new cases of amyotrophic lateral sclerosis and parkinsonism-dementia was conducted by follow-up of 899 Chamorros in the Mariana Islands who participated in a baseline medical examination and interview in 1968. During a 15-year follow-up period, 28 new neurologically confirmed cases occurred, including 23 with parkinsonism-dementia and five with amyotrophic lateral sclerosis. The low incidence of amyotrophic lateral sclerosis was consistent with the reported disappearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 0 publications
3
46
0
Order By: Relevance
“…Both these theories could agree with the epidemiological finding reported above that the only risk factor for ALS-PDC on Guam and Rota identified among 23 investigated factors was the preference for traditional Chamorro food (Reed et al, 1987).…”
Section: Ups and Downs For The Hypothesis Of A Dietary Cause Of Als-psupporting
confidence: 91%
See 3 more Smart Citations
“…Both these theories could agree with the epidemiological finding reported above that the only risk factor for ALS-PDC on Guam and Rota identified among 23 investigated factors was the preference for traditional Chamorro food (Reed et al, 1987).…”
Section: Ups and Downs For The Hypothesis Of A Dietary Cause Of Als-psupporting
confidence: 91%
“…Reed et al (1987) observed a higher than expected occurrence of both ALS and PD in Filipino migrants to Guam, as long as 29 years after their arrival. noted that of six Filipino and three US white men who arrived to the island and subsequently developed motor neuron disease, seven arrived in the late 1940s, one in 1956 and one in 1963.…”
Section: Searching For An Environmental Cause For Als On Guammentioning
confidence: 48%
See 2 more Smart Citations
“…ALS-PDC incidence among the Chamorro people was about 100 times higher than in the continental United States [40], and was related to the Chamorro traditional diet, of which cycad seeds were a main constituent [41]. BMAA was found in dietary items such as cycad flour that was prepared from washed seeds, and flying foxes, a bat species that foraged on cycad seeds and that was regarded as a delicacy by the Chamorro people [42,43].…”
Section: The Role Of Bmaa In the Aetiology Of Neurodegenerative Diseasesmentioning
confidence: 99%